1998
DOI: 10.1093/emboj/17.14.4114
|View full text |Cite
|
Sign up to set email alerts
|

Snurportin1, an m3G-cap-specific nuclear import receptor with a novel domain structure

Abstract: The nuclear import of the spliceosomal snRNPs U1, U2, U4 and U5, is dependent on the presence of a complex nuclear localization signal (NLS). The latter is composed of the 5'-2,2,7-terminal trimethylguanosine (m3G) cap structure of the U snRNA and the Sm core domain. Here, we describe the isolation and cDNA cloning of a 45 kDa protein, termed snurportin1, which interacts specifically with m3G-cap but not m7G-cap structures. Snurportin1 enhances the m3G-capdependent nuclear import of U snRNPs in both Xenopus la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
261
0
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(287 citation statements)
references
References 73 publications
(132 reference statements)
10
261
0
8
Order By: Relevance
“…35. Alexa 488-or Cy5-labeled U1 snRNPs were prepared as described (10). Purity, functionality, and integrity of labeled U1 snRNPs were confirmed as described (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35. Alexa 488-or Cy5-labeled U1 snRNPs were prepared as described (10). Purity, functionality, and integrity of labeled U1 snRNPs were confirmed as described (36).…”
Section: Methodsmentioning
confidence: 99%
“…A second component is located at the Sm core but has not been defined precisely yet (9). Recently, an adaptor called Snurportin-1, which interacts specifically with the m 3 G cap of U snRNPs and the receptor karyopherin ␤, has been identified (10).…”
mentioning
confidence: 99%
“…In any event, the adaptor for the TMG cap is called snurportin1 (SPN1); this protein binds directly to the TMG cap and significantly improves the kinetics of snRNP import. 61,64,65 At the time, relatively little was known about the factor that mediates the interaction between the Sm core and importin b. Previous studies had indicated that the Sm core adaptor is a cytosolic factor that binds to Sm proteins and importin b.…”
Section: Smn and Cytoplasmic Snrnp Assemblymentioning
confidence: 99%
“…Nevertheless, some nuclear proteins are known to enter the nucleus by binding to importin ␣ or ␤ via an atypical non-basic sequence (33,34). Alternatively, binding to another nuclear protein may target a protein to the nucleus (35). It is possible that AZ1 enters the nucleus via one of these mechanisms.…”
Section: Fig 7 Mutational Analysis Of Nes2mentioning
confidence: 99%